Supplemental Table S3 from Spatial Transcriptomic Analysis of Ovarian Cancer Precursors Reveals Reactivation of IGFBP2 during Pathogenesis - Yeh Wang (14964041) (2025)
Raw data provided by Nanostring bioinformatic team